2005
DOI: 10.1021/ja051834q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanistic Aspects of the Heck Reaction Promoted by a CN−Palladacycle

Abstract: In the Heck reaction between aryl halides and n-butyl acrylate, the palladacycle {Pd[kappa(1)-C, kappa(1)-N-C=(C(6)H(5))C(Cl)CH(2)NMe(2)](mu-Cl)}(2), 1, is merely a reservoir of the catalytically active Pd(0) species [1](Pd colloids or highly active forms of low ligated Pd(0) species) that undergoes oxidative addition of the aryl halide on the surface with subsequent detachment, generating homogeneous Pd(II) species. The main catalytic cycle is initiated by oxidative addition of iodobenzene to [1], followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(112 citation statements)
references
References 71 publications
4
105
2
1
Order By: Relevance
“…4 Um belo trabalho de investigação sobre aspectos mecanísticos do acoplamento de Heck, promovido por ciclopaladatos, foi apresentado por Dupont. 11 Nele foi avaliada a influência do grupo substituinte em brometos de arila na reação com acrilato de n-butila através de quatro ciclopaladatos. Os resultados mostraram uma lineariedade satisfatória (R 2 = 0,98) quando σ o era aplicado para todas as quatro fontes de paládio, fornecendo ρ = 2,5.…”
Section: Resultsunclassified
“…4 Um belo trabalho de investigação sobre aspectos mecanísticos do acoplamento de Heck, promovido por ciclopaladatos, foi apresentado por Dupont. 11 Nele foi avaliada a influência do grupo substituinte em brometos de arila na reação com acrilato de n-butila através de quatro ciclopaladatos. Os resultados mostraram uma lineariedade satisfatória (R 2 = 0,98) quando σ o era aplicado para todas as quatro fontes de paládio, fornecendo ρ = 2,5.…”
Section: Resultsunclassified
“…Analogous to several other publications dealing with Pd-or Ni-NPs, it is possible that the Cu 2 O-NPs act as a catalyst reservoir for Cu(I), and a molecular species might act as the active species. 32,51 There are different ways of how a molecular species can theoretically be leached from the particle surface as Beletskaya and co-workers have revealed. Usually there is an equilibrium between leaching and the Ostwald-ripening of the particles.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…28 Ionic liquids (ILs) are widely known as so-called "designer solvents". They can act as promoters and activators, 29,30 as protecting agents and stabilisers, 28,[30][31][32][33][34][35] as reducing agents 11,30,35 and certainly as (co-)solvents themselves for molecular and nanoscale species. [36][37][38][39] Only limited reports about the use and influence of ionic liquids as solvents for nanocatalytic C-N cross coupling reactions are known.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in many contributions, authors have identified catalysis by soluble species but could not rule out some catalysis by supported sites. The Hg(0) test is capable of extinguishing catalysis by free Pd(0), [8,[22][23][24]26,40,41] although it is not believed that it can discriminate between heterogeneous, macroscopic palladium particles, soluble palladium nanoparticles, or homeopathic [35,36,42,43] palladium (vide supra). [8] What is needed is a poison that is selective for leached, homogeneous species.…”
Section: Introductionmentioning
confidence: 99%